2017
DOI: 10.1016/j.mce.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol protects against the effects of a high fat diet on cardiac glucose, lipid and nitric oxide metabolism in rats

Abstract: Please cite this article as: Zafirovic, S., Obradovic, M., Sudar-Milovanovic, E., Jovanovic, A., Stanimirovic, J., Stewart, A.J., Pitt, S.J., Isenovic, E.R., 17β-Estradiol protects against the effects of a high fat diet on cardiac glucose, lipid and nitric oxide metabolism in rats, Molecular and Cellular Endocrinology (2017), doi: 10.1016/j.mce.2017 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Our previous study confirmed that estrogen protects endothelial cells and delays cellular senescence, and subsequent studies confirmed the role of estrogen in protecting cardiac function 33,34. However, the long-term usage of estrogen can lead to serious side effects such as increasing the risk of stroke, breast cancer, ovarian cancer, and others 13,14,35.…”
Section: Discussionsupporting
confidence: 75%
“…Our previous study confirmed that estrogen protects endothelial cells and delays cellular senescence, and subsequent studies confirmed the role of estrogen in protecting cardiac function 33,34. However, the long-term usage of estrogen can lead to serious side effects such as increasing the risk of stroke, breast cancer, ovarian cancer, and others 13,14,35.…”
Section: Discussionsupporting
confidence: 75%
“…Animal studies suggest that hyperglycemia can cause the release of RHs decrease. Similar with the relationship between RHs and hyperglycemia, some researchers concluded that the decreased testosterone level means the increase of the serum TC level for testosterone is synthesized from cholesterol. , The CPF may induce the metabolism syndrome by reducing the testosterone concentration, for testosterone can regulate lipid and glucose metabolism in adipose tissues, muscle, and liver, may reduce E 2 , and leads to obesity or T2DM in mammals for E 2 can change VLDL and TG levels, which are greatly related to obesity and T2DM, may alter FSH and LH levels, and then increase the LDL level and retard the LDL-C circulating level, subsequently resulting in obesity or T2DM. , …”
Section: Cpf Can Induce Rh Changes and Lead To Metabolic Alterationsmentioning
confidence: 82%
“…Zafirovic et al, (24) showed that obesity, in addition to hindering glucose uptake and insulin signaling in the heart, elevates the production of NO in the heart through the increase in the expression of inducible nitric oxide synthase (iNOS). (24) Nitric oxide is an important vasodilator and directly influences cardiac contractility.…”
Section: ❚ Discussionmentioning
confidence: 99%
“…Zafirovic et al, (24) showed that obesity, in addition to hindering glucose uptake and insulin signaling in the heart, elevates the production of NO in the heart through the increase in the expression of inducible nitric oxide synthase (iNOS). (24) Nitric oxide is an important vasodilator and directly influences cardiac contractility. (25) However, from a biochemical point of view, NO can react with the superoxide anion, preventing it from being dismuted by superoxide dismutase (SOD) in H 2 O 2 .…”
Section: ❚ Discussionmentioning
confidence: 99%